Modulation of pain sensitivity by tDCS using different anodal connector locations: a single-blinded, randomized, sham-controlled study - Tsai, Shang-Yueh; Lin, Yi-Ru; Niddam, David M. (Frontiers in Pain Research, 2025)
BackgroundThe efficacy of transcranial direct current stimulation (tDCS) depends on various stimulation parameters. With rectangular electrodes, the location of the wire connector may affect the electrical field relative to the underlying target area. Here, we examined longitudinal changes in pain sensitivity and GABA levels in response to tDCS using standard rectangular (5 × 7 cm) electrodes and two different anodal connector locations.MethodsIn this single-blinded, randomized, sham-controlled study, 53 healthy volunteers were assigned to one of 4 groups, receiving either real tDCS or sham tDCS, with the anodal connector oriented either superior-medially or ventral-laterally. tDCS was delivered on 5 consecutive days with the anode and cathode placed over the left primary sensorimotor cortex (SM1) and the right dorsolateral prefrontal cortex, respectively. Pain detection thresholds (PT) and moderate pain thresholds (MPT) of the right index finger and GABA levels from the bilateral SM1 were obtained prior to tDCS, after 5 tDCS sessions, and after 6 weeks.ResultsSuperior-medial oriented tDCS significantly increased both pain thresholds at day 5 and at 6 weeks, whereas ventral-lateral oriented tDCS or sham tDCS did not. At day 5, MPT was significantly increased when comparing superior-medial oriented tDCS with sham tDCS. At week 6, both thresholds were significantly increased when comparing superior-medial oriented tDCS with ventral-lateral oriented tDCS and MPT was also increased when comparing superior-medial oriented tDCS with sham tDCS. GABA levels did not differ between time-points or between groups and no association was found between baseline GABA levels in the stimulated hemisphere and change in pain thresholds.ConclusionstDCS-induced long-lasting changes in pain sensitivity may depend on the location of the wire connector when using a rectangular anode. A greater pain modulatory effect may be induced when the connector is aligned superior-medially along the central sulcus.